SURFACE MICROTOPOGRAPHY OF SUDOITE - Jige M.; Kitagawa R.; Zaykov V.V.; Sinyakovskaya I. (My University, 2003)
The gold-decoration technique of electron microscopy is used to study the surface microtopography of natural (001) surfaces of sudoite collected from a hydrothermal vein of the Berezovsk gold deposit, Central Urals, Russia. Only closed step patterns with malformed and/or nearly circular islands were observed on the (001) growth surface of sudoite crystals, implying a two-dimensional nucleation mechanism. This is in contrast to the spiral step patterns commonly recognized on growth surfaces of other clay minerals, such as illite and kaolinite, formed under hydrothermal conditions. It is inferred that the crystallization of sudoite occurred under relatively higher temperatures and/or from more highly supersaturated fluids than many other hydrothermal clay minerals so far described.
Keywords: Sudoite